(untitled) (American Journal of Islam and Society, 2000)
Presented here is an analysis of the political thought of Ahmet Agaoglu, one of the sounding boards of Mwtafa Kemal Atatiirk. In his utopian work “In the Land of Free People,’’ he is preoccupied with the idea of making Turkey a “progressive” state so that it can attain the standard achieved by Western civilization. How it is done does not matter, as long as the country is put on the path of “liberalism,” which to him is the shortcut to development. The liberalism suggested by Agaogu is not via privileging individual rights through popular will (as in the West), but through manipulation by the state; even if it must be achieved through despotic practices.